استراتيجيات ترجمة الصور الفنية من اللغة الفرنسية إلى اللغة العربية دراسة تطبيقة - أيت إحدادن, كريمة (Maalim, 2026)
the process of translating literary texts as novel, theater, poetry and stories is one of the most difficult translations compared to scientific texts, the writer of literary text does not depend on the simple style used by the general public, because the poet or the prose writes in a manner that reflects his sensitivity and his large imagination, in addition to the implication of a symbolic language in the poetic text which makes it difficult to dismantle, so the translator of literary genres must create parallel creations while translating into the target language in order to preserve its literature, its esthetics and luster, but what are the strategies for translating literary style? .